Сlinical features of left atrial myxoma in comorbidity with active lung tuberculosis - M. Yu. Kolesnyk; O. V. Nikityuk; O. V. Komarova-Laz’ko; S. N. Gulevskij; A. M. Kiosov (Patologìâ)
The symptoms and syndromology of myxomas with clinical features of a rare comorbidity – lung tuberculosis and left atrial myxoma in a 69-old year woman, are described in the article. The description includes the clinical history, transesophageal echocardiography findings, pathomorphological characteristics of myxoma, also photoillustrations of tumor’s macro- and microstructures. The analysis reflects the troubles in differential diagnosis of the clinical case due to non-specific symptoms of both diseases. The discussion provides the information about the possible pathophysiological link between myxoma and tuberculosis and the role of interleukin6 inthis process.